Preleminary Study: The Effects of Different Cryoprotectants on Damage and Hatching Rates of African Catfish (Clarias gariepinus) - Akhmad Taufiq Mukti; Septuresty Hartri Eka; Woro Hastuti Satyantini; Ahmad Shofy Mubarak (Department of Aquaculture, 2020)
This study was aimed to observe the effects of different cryoprotectants in embryo cryopreservation on damage and hatching rates of African catfish (Clarias gariepinus) embryo. The gastrula-staged embryos were treated 5% (v/v) solutions concentration of dimethyl sulfoxide (DMSO), propylene glycol (PG), honey, and combined cryoprotectants, respectively and preserved at temperatures of 4 and 0ºC for 30 min, 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, respectively. Thawing of embryos was conducted in freshwater at a temperature of 28ºC. Then, the embryos were incubated in the aquaria at 28ºC temperature. The result showed that the different cryoprotectants in gastrula-staged embryo cryopreservation affect damage and hatching rates of African catfish embryos at different length of preservation. The percentage of catfish embryo damage increases with different length of preservation and the storage temperature. A combination of DMSO-honey and PG-honey has the lowest damage percentage and the highest hatching rate of catfish embryo compared to other treatments (p<0.05).